Defining a therapeutic target for pallidal deep brain stimulation for dystonia. Issue 1 (18th June 2014) - Cheung, Tyler; Noecker, Angela M.; Alterman, Ron L.; McIntyre, Cameron C.; Tagliati, Michele
<x xml:space="preserve">Abstract</x> Objective To create a data‐driven computational model that identifies brain regions most frequently influenced by successful deep brain stimulation (DBS) of the globus pallidus (GP) for advanced, medication‐resistant, generalized dystonia. Methods We studied a retrospective cohort of 21 DYT1 primary dystonia patients treated for at least 1 year with bilateral pallidal DBS. We first created individual volume of tissue activation (VTA) models utilizing neuroimaging and postoperative stimulation and clinical data. These models were then combined into a standardized probabilistic dystonia stimulation atlas (DSA). Finally, we constructed a candidate target volume from electrodes demonstrating at least 75% improvement in contralateral symptoms, utilizing voxels stimulated by least 75% of these electrodes. Results Pallidal DBS resulted in a median contralateral hemibody improvement of 90% (mean = 83%, standard deviation [SD] = 20) after 1 year of treatment. Individual VTA models of the 42 active electrodes included in the study demonstrated a mean stimulation volume of 501mm3 ([SD] = 284). The resulting DSA showed that areas most frequently stimulated were located squarely in the middle of the posterior GP, with a common target volume measuring 153mm3. Interpretation Our results provide a map of the region of influence of therapeutic DBS for dystonia and represent a potential target to refine current methods of surgical planning and stimulation parameters selection. Based on their role in alleviating symptoms, these regions may also provide anatomical and physiological information relevant to disease models of dystonia. Further experimental and clinical studies will be needed to validate their importance. Ann Neurol 2014;76:22–30